Mechanism of actin filament pointed end capping by tropomodulin - Rao, Jampani Nageswara (Science, 2014)
Proteins that cap the ends of the actin filament are essential regulators of cytoskeleton dynamics. While several proteins cap the rapidly-growing barbed end, tropomodulin (Tmod) is the only protein known to cap the slowly-growing pointed end. The lack of structural information severely limits our understanding of Tmod’s capping mechanism. We describe crystal structures of actin complexes with the unstructured N-terminal and the leucine-rich repeat C-terminal domains of Tmod. The structures and biochemical analysis of structure-inspired mutants showed that one Tmod molecule interacts with three actin subunits at the pointed end, while also contacting two tropomyosin molecules on each side of the filament. We found Tmod achieves high affinity binding through several discrete low-affinity interactions, which suggests a mechanism for controlled subunit exchange at the pointed end.